Injury and illness in elite athletics: a prospective cohort study over three seasons - Kelly, S.; Pollock, N.; Polglass, G.; Clarsen, B. (British Journal of Sports Medicine, 2021)
Background Athletics is one of the most popular sports in the world and is the centrepiece of the Summer Olympic Games. Participation in athletics training and competition involves a risk of illness and injury.